O enriquecimento sem causa no código civil brasileiro - Leite, Adriano Pugliesi (2008)
The unjust enrichment in the Brazilian Civil Code is viewed as a source of obligations and a principle of Civil Law. The Civil Code of 2002 defined the term of unjust enrichment, in an innovative and autonomous manner, as a source of obligatons in the form of a unilateral act (arts. 884 to 886). At the same time, unjust enrichment existed before the publishing of this Code and remains in existance as a general principle of Civil Law. The present work has, as its objective, the analysis of historical aspects that resulted in the legal establishment of the term as a source of obligations, the main theories surrounding the theme, as well as the analysis of normative dispositions of the Brazilian Civil Code and its position in international judicial order, relating its fundamental principles to the manner in which it is applied. Therefore, the work intends to analyse the general characteristics of the term, its reach within Private Law, relating hypotheses of the configuration of the term expressed in the Brazilian Civil Code and examples of its application in Brazilian jurisprudence. The development of the project demonstrates that unjust enrichment has a large and growing importance in the Brazilian legal context, presenting itself as an important tool to render balance and justice to private dealings. The methodological direction used lies in judicial/dogmatic principles, since the intention is to analyse legal norms and their repercussion on the presented theme. In some aspects, it comes close to judicial/theoretical methodology, considering the social relevance that surrounds the term under scrutiny. As to the generic investigation types, the judicial/descriptive method predominates, since this work has, as its main objective, the interpretation of legal terms, not eliminating the possibility of judicial/progressive research, inasmuch as the study may lead to future tendencies concerning the application of the measure. The hypothetical/deductive method is applied, in which a theme is proposed and an analysis of the development of its characteristics is requested. The conclusions about the theme are relative and result from the argumentation structure presented in this dissertation, without disconsidering the fundaments of other studies, especially because it is a term whose comprehension is increasing with every new day